Editorial. (13th April 2023) - Batty, Craig
This editorial introduces the 14.1 issue of the Journal of Screenwriting . It provides an overview of the articles in the issue and makes reference to the 2022 Screenwriting Research Network (SRN) conference held at the University of Vienna, which was the first face-to-face conference of the SRN in three years.